2005
DOI: 10.1111/j.0013-0133.2005.00983.x
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in Reported Well‐Being: Evidence from Twelve European Countries

Abstract: Résumé:Dans cet article nous modélisons la relation entre le revenu et le bien-être déclaré à l'aide de techniques à effet aléatoire appliquées sur des données de panel issues de douze pays européens. Il n'est pas possible de distinguer empiriquement une hétérogénéité des fonctions d'utilité (transformation du revenu en utilité) et une hétérogénéité des fonctions d'expression (transformation de l'utilité en bien-êttre déclaré); néanmoins, nous montrons que l'on peut fermement rejeter l'hypothèse selon laquelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
134
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 189 publications
(137 citation statements)
references
References 30 publications
3
134
0
Order By: Relevance
“…Notes 1 A related approach has been previously applied by Clark et al (2005) in the context of estimating the responses of well-being to income changes.…”
Section: Resultsmentioning
confidence: 99%
“…Notes 1 A related approach has been previously applied by Clark et al (2005) in the context of estimating the responses of well-being to income changes.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the impact of income on SWB is identified to be positive, though subject to some considerable discussion arising from the 'Easterlin paradox' [14], in which rising real incomes have not been correlated with rising levels of SWB over time. Yet, crosssectional studies identify a positive effect of income on SWB [4,37] as do panel data studies [8,16,17,21,41]. An explanation offered by Frey and Stutzer [19] is that it is relative income that ultimately affects SWB because of the relativity of individual's judgments.…”
Section: State Of Researchmentioning
confidence: 99%
“…A recent example for such an approach is the study by Clark et al (2005) who used GLS data from the European Community Household Panel. They found that the effect of income changes were larger in the "latent satisfied" than in the "latent dissatisfied" classes.…”
mentioning
confidence: 99%